2008
DOI: 10.1002/bmc.1085
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of main taxoids in Taxus needles extracts by solid‐phase extraction‐high‐performance liquid chromatography with pentafluorophenyl column

Abstract: A simple and accurate RP-HPLC method with pentafluorophenyl (PFP) column was developed for the simultaneous determination of six taxoids, i.e. paclitaxel, 10-deacetylbaccatin III (10-DAB III), 7-xylosyl-10-deacetyltaxol (7-xyl-10-DAT), 10-deacetyltaxol (10-DAT), cephalomannine and 7-epi-10-deacetyltaxol (7-epi-10-DAT), in the extracts from the needles of three Taxus species. The mobile phase consisted of acetonitrile (A) and water (B), and the extracts were separated using gradient elution program: 30% A at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…Its content in yew trees is as much as 0.5% (dry weight of the bark)18. XDT content is even higher than that of Taxol in nursery cultivated yew trees1920. This analogue is usually discarded during Taxol extraction, causing both resource waste and potential environmental pollution.…”
mentioning
confidence: 99%
“…Its content in yew trees is as much as 0.5% (dry weight of the bark)18. XDT content is even higher than that of Taxol in nursery cultivated yew trees1920. This analogue is usually discarded during Taxol extraction, causing both resource waste and potential environmental pollution.…”
mentioning
confidence: 99%
“…In contrast, the extraction yields of seven taxanes decreased with high water content of 50–100%. Interestingly, when compared with 80% ethanol usually used for the extraction of taxanes [4,5], the 80% water content in the natural aqueous DES showed a similar extraction efficiency for the 10‐DAB III and higher extraction efficiency for the other six taxanes. Considering that 80% water content of the prepared aqueous DES has the characteristics of less solvent consumption, better extraction efficiency, and is eco‐friendly, we chose the menthol‐based aqueous DES with 80% water volume and only 20% menthol/1‐propanol for sample preparation of taxanes.…”
Section: Resultsmentioning
confidence: 99%
“…Paclitaxel, a natural diterpenoid alkaloid with distinct chemical structure, was initially isolated from the bark of Taxus brevifolia [1,2] and considered as a natural anticancer drug used to cure malignant tumors such as breast, ovarian, lung, and non‐small cell lung cancer [3–6]. After a period of clinical application, it has been found that as an active ingredient of a medicinal plant, there were a series of problems in the development of paclitaxel drugs, such as paclitaxel production is still very far away to meet the needs for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile phase consisted of ACN (A) and water (B). Based on previous research [50], baseline separation of paclitaxel and other taxoids was achieved with a gradient elution program as follows: 25% A at the first 17 min, and then ramped to 37% A at 18 min, held until 58 min. The UV detector was set at the wavelength of 234 nm.…”
Section: Hplc Analysis Of Four Taxoidsmentioning
confidence: 99%